(untitled) (Research, Society and Development, 2022)
The large number of dirt roads and their difficult access are factors that contribute to the difficulty of the municipalities to perform the necessary maintenance on the local roads, causing the most distant communities to be affected in several factors, whether in the difficulty of locomotion or in the lack of basic sanitation. It is worth pointing out that these unpaved roads are of great importance to the rural dwellers, because it is through them that this sphere has access to basic services. In view of the recognition of such difficulties for the maintenance of the vicinal roads, a study and mapping about the dirt roads and the Laterite and sand deposits in the municipality of Açailândia - MA was carried out. From the mapping of the deposits found in the region can be seen that the deposit A, among the deposits of sand, is the one that has the greatest possibility of displacement for being the holder of 79 km of dirt road in its field of proximity to do the maintenance of roads in the municipality in the ZTU, thus enabling a more viable maintenance in relation to other roads. In addition, it was also observed that between deposits C and D there was no great competition between them because they are very close.